Russian Federation : Technical Note on Stress Testing of the Banking Sector. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This technical note focuses on the stress testing exercise in 2010 for the financial sector assessment program based on the existing approaches of the Central Bank of Russia, as well as a separate bottom-up exercise. The tests covered broad ranges of risk factors. The single factor tests examined instantaneous impact of credit, concentration, market, liquidity, and interbank contagion risks. The results of the stress tests suggested that the Russian banking system is, on the whole, resilient to a variety of macroeconomic and financial shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet